PERBANDINGAN EFEK TERAPI ANTIHIPERTENSI PADA PASIEN PROLANIS DI KABUPATEN BANYUMAS - tunjung winarno (Parapemikir : Jurnal Ilmiah Farmasi, 2021)
This study aims to determine the pattern of hypertension therapy, the effectiveness of monotherapy and combination therapy, to determine the relationship between patient characteristics and therapy with the effectiveness of hypertension therapy in Prolanis patients in Banyumas, with used a descriptive analytic design. Data were collected retrospectively for 4 months and 1 month prospectively. The population in this study was all hypertensive patients participating in Prolanis at 12 health centers in  Banyumas. Sampling was done using total sampling. The sample size  was 287 hypertensive patients participating in Prolanis in June-September and November 2019. The pattern, namely that the most widely used antihypertensive therapy was monotherapy CCB(amlodipine) as much as 27.9%, ARB (Candesartan) as much as 14.3%, and combination drugs of CCB class with ARB as much as 14.3%. The effectiveness of antihypertensive therapy CCB 19.9% of patients, ARB 10.1% of patients, CCB and ARBs 10.1% of patients. Based on the results of the Kruskal Wallis test, it shows that there is a difference in the average systolic BP with a value of p = 0.000 and there is no difference in the average diastolic BP with a value of p = 0.132. The results of the Pearson and Spearman correlation test showed that the factors associated with the patient's systolic and diastolic BP were diet (p pearson : 0.03), BMI (p Spearman : 0.005), adherence (pearson value : 0.032), and ESO (spearman p value : 0.035). The correlation coefficient for all of these factors was obtained as very low values 0.5 which indicated that the relationship between diet, BMI, adherence, and ESO with the patient's mean systolic and diastolic BP was very weak.